Relationship of E-Commerce, Influencer Marketing and Social Media to Digital Marketing (Marketing Management Literature Review) - Rajab, Muhammad (Dinasti International Journal of Economics, Finance & Accounting, 2021)
The Literature Review article on the Relationship of E-Commerce, Influencer Marketing and Social Media to Digital Marketing is a scientific article that aims to build a research hypothesis on the influence between variables that will be used in further research, within the scope of Marketing Management. The method of writing this Literture Review article is using the library research method, which is sourced from online media such as Google Scholar, Mendeley and other academic online media. The results of this study are: 1) E-Commerce is related to Digital Marketing; 2) Influencer Marketing is related to Digital Marketing; and 3) Social Media related to Digital Marketing. Apart from these 3 exogenous variables that affect the endogenous variables, there are many other factors including the display of advertising, word of mouth and event marketing variables.